2004
DOI: 10.1002/pros.20023
|View full text |Cite
|
Sign up to set email alerts
|

YB‐1 is upregulated during prostate cancer tumor progression and increases P‐glycoprotein activity

Abstract: We hypothesize that early in prostate cancer progression, increased expression of YB-1 may increase P-gp activity which may in turn lower androgen levels in the prostate tumor cells. Suppression of androgen levels may activate cell survival pathways and lead to an adaptive survival advantage of androgen independent prostate cancer cells following androgen ablation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
114
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 39 publications
10
114
0
1
Order By: Relevance
“…Elevated levels of the transcription elongation factor TCEB1͞Elongin C are associated with advanced androgen-independent prostate cancers (20), and changes in the subcellular localization of the membrane metalloendopeptidase MME͞CD10 expression are linked to prostate cancer grade (21). Immunohistochemical analysis of the Akt-regulated transcriptional repressor NSEP͞YB-1 demonstrates a strong positive correlation with Gleason grade (22). NSEP͞YB-1 may influence cancer progression through multiple mechanisms that include enhancement of anchorage-independent cell growth and upregulation of the p-glycoprotein multidrug-resistance protein (22,23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of the transcription elongation factor TCEB1͞Elongin C are associated with advanced androgen-independent prostate cancers (20), and changes in the subcellular localization of the membrane metalloendopeptidase MME͞CD10 expression are linked to prostate cancer grade (21). Immunohistochemical analysis of the Akt-regulated transcriptional repressor NSEP͞YB-1 demonstrates a strong positive correlation with Gleason grade (22). NSEP͞YB-1 may influence cancer progression through multiple mechanisms that include enhancement of anchorage-independent cell growth and upregulation of the p-glycoprotein multidrug-resistance protein (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemical analysis of the Akt-regulated transcriptional repressor NSEP͞YB-1 demonstrates a strong positive correlation with Gleason grade (22). NSEP͞YB-1 may influence cancer progression through multiple mechanisms that include enhancement of anchorage-independent cell growth and upregulation of the p-glycoprotein multidrug-resistance protein (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemistry has established an association between high levels of nuclear YB-1, tumor progression and drug resistance; nuclear YB-1 is therefore regarded as a poor prognostic indicator of patient outcome (Oda et al, 1998(Oda et al, , 2003Shibahara et al, 2001;Kohno et al, 2003;Gimenez-Bonafe et al, 2004;Chatterjee et al, 2008). We sought to evaluate the proposed proteolytic mechanism of YB-1 nuclear activation, given its direct relevance to the validity of the numerous immunohistochemical studies performed with C-terminal YB-1 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…MDR1 induction by YB-1 is manifest by the correlation between drug resistance of breast cancers and YB-1 overexpression (Bargou et al, 1997). Furthermore, immunohistochemical analysis of a variety of drug-resistant cancers and cell lines has established a relationship between nuclear YB-1, tumor drug resistance and poor patient outcome (Oda et al, 1998(Oda et al, , 2003Shibahara et al, 2001;Kohno et al, 2003;Gimenez-Bonafe et al, 2004;Chatterjee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal YB-1 staining has been found in several cancer types, including breast cancer (Bargou et al, 1997), osteosarcoma (Oda et al, 1998), ovarian adenosarcoma (Kamura et al, 1999), colorectal carcinoma (Shibao et al, 1999), lung cancer (Gu et al, 2001), and prostate cancer (Gimenez-Bonafe et al, 2004). Nuclear localization of YB-1 in breast tumor samples correlated with expression of the multidrug resistance gene MDR1 (Bargou et al, 1997) and YB-1 was found to be directly involved in MDR1 gene activation in response to genotoxic stress .…”
Section: Introductionmentioning
confidence: 99%